What are the appropriate axioms of rationality for reasoning under uncertainty with resource-constrained systems?. (2020) - Atmanspacher, Harald; Basieva, Irina; Busemeyer, Jerome R.; Khrennikov, Andrei Y.; Pothos, Emmanuel M.; Shiffrin, Richard M.; Wang, Zheng
Abstract: When constrained by limited resources, how do we choose axioms of rationality? The target article relies on Bayesian reasoning that encounter serious tractability problems. We propose another axiomatic foundation: quantum probability theory, which provides for less complex and more comprehensive descriptions. More generally, defining rationality in terms of axiomatic systems misses a key issue: rationality must be defined by humans facing vague information.